Magnetic resonance imaging arterial‐spin‐labelling perfusion alterations in childhood migraine with atypical aura: a case–control study. (6th April 2016) - Boulouis, Grégoire; Shotar, Eimad; Dangouloff‐Ros, Volodia; Grévent, David; Calmon, Raphaël; Brunelle, Francis; Naggara, Olivier; Kossorotoff, Manoelle; Boddaert, Nathalie
Abstract : Aim: Atypical migraine with aura can be challenging to diagnose. Arterial‐spin‐labelling (ASL) is able to non‐invasively quantify brain perfusion. Our aim was to report cerebral blood flow (CBF) alterations using ASL, at the acute phase of atypical migraine with aura in children. Method: Paediatric patients were retrospectively included if (1) referred for acute neurological deficit(s), (2) underwent brain magnetic resonance imaging (MRI) at presentation with ASL sequence, and (3) had subsequent diagnosis of migraine with aura. Neurological symptom‐free controls were matched for age. Twenty‐eight regions of interest (ROIs) were drawn on CBF maps for each participant/control. Results: Ten patients were included (median age 13y, range 8–16y). Eight of 10 had multiple aura symptoms during the episode. For every patient, CBF was decreased in a brain region consistent with symptoms when MRI was performed less than 14 hours after onset ( n =7 patients) and increased if the MRI was performed 17 hours or more after ( n =4 MRIs). Interpretation: MRI–ASL appears to be a promising tool for the diagnostic workup and differentials exclusion in paediatric migraine with aura. Constant and time‐consistent non‐territorial CBF modifications were found in our sample providing additional insight to migraine with aura pathophysiology. The authors encourage implementing this sequence at the acute phase of unexplained paediatric neurological deficits, with or without accompanying headache. What this paper adds: Children presenting at the acute phase of migraine with aura present measurable alterations of regional cerebral blood flow (CBF) using arterial‐spin‐labelling (ASL) sequence. CBF alterations are related to time post onset, not persistence of symptoms at time of magnetic resonance imaging. Patients scanned early show hypoperfusion and those scanned late show hyperperfusion, regardless of symptoms at the time of imaging. This article is commented on by Abu‐Arafeh on pages897–898 of this issue.